2009
DOI: 10.1111/j.1548-1425.2009.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

A pre‐event configuration for biological threats: Preparedness and the constitution of biosecurity events

Abstract: Drawing on an inquiry into Israel's preparedness for biological threats, in this article I suggest a new analysis of biosecurity events. A complex and dynamic assemblage emerges to prepare for biological threats, one that I call a “pre‐event configuration.” The assemblage is composed of three core elements—the scientific element, the security element, and the public health element—each of which diagnoses threats and suggests appropriate solutions. This configuration also determines what will be perceived as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Based on speculation about such factors as the environment, health, and capital, anticipation is intricately associated with a logic of disaster management and attempts to prepare for a future defined by risk. Anthropologists have shown that administrators and planners increasingly respond to this futurity and its dimension of risk through ‘prognosis’ (Mathews and Barnes, 2016), regimes of preparedness (Samimian‐Darash, 2009), and manipulations of time (Guyer, 2007). When they conflate disaster with national security, regimes of anticipation increase government control over spaces, populations, and bodies (Lakoff and Collier, 2008; Collier and Lakoff, 2015).…”
Section: The Emotional Lives Of Disastersmentioning
confidence: 99%
“…Based on speculation about such factors as the environment, health, and capital, anticipation is intricately associated with a logic of disaster management and attempts to prepare for a future defined by risk. Anthropologists have shown that administrators and planners increasingly respond to this futurity and its dimension of risk through ‘prognosis’ (Mathews and Barnes, 2016), regimes of preparedness (Samimian‐Darash, 2009), and manipulations of time (Guyer, 2007). When they conflate disaster with national security, regimes of anticipation increase government control over spaces, populations, and bodies (Lakoff and Collier, 2008; Collier and Lakoff, 2015).…”
Section: The Emotional Lives Of Disastersmentioning
confidence: 99%
“…An assemblage, in contrast, is heterogeneous, dynamic, and does not represent a major response. Rather, it can be characterized by numerous sub-structures that exist simultaneously (see also Samimian-Darash, 2009). 3.…”
Section: Discussionmentioning
confidence: 99%
“…These imaginings thus have long‐term consequences (Gusterson ; Lowe ; Nelson et al. ; Samimian‐Darash ; Schoch‐Spana ). In this article, rather than focusing on how people imagined and prepared for events, I look at how people continued their engagements with infectious microbes after the H1N1 epidemic.…”
Section: Historical and Cultural Contexts Of Bioseguridadmentioning
confidence: 99%